PHYTOCHEMICAL ANALYSIS AND ANTIBACTERIAL EFFICACY OF EXTRACTS OF DIPTEROCARPUS ZEYLANICUS - Samad, Shamaa Abdul; Silva, Sadin W (LIFE: International Journal of Health and Life-Sciences, 2021)
<span style="color: rgba(0, 0, 0, 0.87); font-family: 'Noto Sans', -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The overuse of antibiotics has resulted in microorganisms developing resistance to commercially available antibiotics. The present research aims to study the presence, properties, and distribution of bioactive compounds within several plant parts of Dipterocarpus zeylanicus which has been used in traditional medicine to treat various infectious diseases. The secondary metabolites were extracted from the leaf, seed, heartwood, and resin through sequential extraction. A qualitative phytochemical investigation was performed to determine the presence of secondary metabolites in the extracts. Antioxidant activity was determined using DPPH radical scavenging assay and Folin-Ciocalteu assay was used to measure the Total polyphenolic content (TPC). The antimicrobial assay was performed using EUCAST disc diffusion assay with Escherichia coli, MRSA, and Staphylococcus aureus as microbial strains. The phytochemical study indicated ubieties of alkaloids, steroids, saponins, flavonoids, cardiac glycosides, phenols, tannins, and terpenoids. Heartwood extracted using ethyl acetate showed the highest antioxidant activity (IC50 0.484 µg/ml). The highest amount of phenols (56.3±4.6 mg GAE/g) was present in the methanol extract of seed. A large inhibition zone (10.7±0.6 mm) by ethyl acetate extract of seed against E. coli demonstrated effective antibacterial activity. Therefore, these crude extracts can be used to isolate novel biologically active secondary metabolites exhibiting antimicrobial and antioxidant properties.